Analysis of Ovary Cancer in the Gynecology Room - Wandira, Nur Ayu; Dinengsih, Sri; Novelia, Shinta (Universitas Islam Lamongan, 2023)
Ovarian cancer is the most common cancer in Indonesian women, with an incidence rate of 14,896 cases in 2020 and a mortality rate of 9,581 cases. According to data from Global Cancer Incidence, Mortality and Prevalence (Globocan), ovarian cancer is the most common cancer among Indonesian women, with an incidence rate of 14,896 cases in 2020 and a mortality rate of 9,581 cases. To determine the factors that influence the incidence of ovarian cancer in patients in the Gynecology Room of the Gatot Soebroto Army Hospital in 2022. Methods: This research is a quantitative study with a case-control design, using primary data with a sample of 54 patients on the 2nd floor of the Gynecology Room. The sampling technique used random sampling. Data analysis using univariate and bivariate using chi square. Research Results: 27 respondents (50%) had ovarian cancer. Variables related to the incidence of ovarian cancer were genetic history (0.000), history of contraception (0.001) and smoking history (0.005) while variables that were not related were obesity (0.268) and age of menarche (776). there is a relationship between genetic history, contraceptive history and smoking history with the incidence of ovarian cancer. It is hoped that women will increase their knowledge about the factors that influence the incidence of ovarian cancer and adopt a healthy lifestyle in their daily activities.